2018
DOI: 10.1016/j.jtcvs.2018.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation impairment after total arch replacement with a stented elephant trunk for type-A dissection

Abstract: Postoperative oxygenation impairment is a common complication of surgery for type-A acute aortic dissection. Body mass index, preoperative oxygenation impairment, preoperative homocysteine, circulatory arrest time, and plasma transfusion were independent risk factors for oxygenation impairment after a total arch replacement procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Our ARD patients required a longer time of ventilation with an extended stay in the ICU, tended to develop pneumonia and underwent tracheotomy more often than NON-ARD patients. This finding is supported by other studies who had similar results [7,8,12]. This study demonstrated that higher age and an increased BMI are risk factors for the development of ARD after acute type A aortic dissection surgery.…”
Section: Plos Onesupporting
confidence: 90%
See 3 more Smart Citations
“…Our ARD patients required a longer time of ventilation with an extended stay in the ICU, tended to develop pneumonia and underwent tracheotomy more often than NON-ARD patients. This finding is supported by other studies who had similar results [7,8,12]. This study demonstrated that higher age and an increased BMI are risk factors for the development of ARD after acute type A aortic dissection surgery.…”
Section: Plos Onesupporting
confidence: 90%
“…In contrast, Girdauskas et al and Chen et al also excluded patients with cardiogenic pulmonary edema, pneumonia, pulmonary embolism or hemo-/pneumothorax [7,8]. Interestingly, studies with a comparable definition of ARD and no defined exclusion criteria showed a similar incidence of 48.5% for ARD [12]. Our ARD patients required a longer time of ventilation with an extended stay in the ICU, tended to develop pneumonia and underwent tracheotomy more often than NON-ARD patients.…”
Section: Plos Onementioning
confidence: 70%
See 2 more Smart Citations
“…Multiple factors could be associated with the development of hypoxemia after TAAD repair, such as dissection-induced inflammatory response, cardiopulmonary bypass, lung atelectasis, and ischemic reperfusion injury [2]. Postoperative hypoxemia prolongs the duration of mechanical ventilation and intensive care unit (ICU) stay, and increases the chances of hospital-acquired pneumonia, re-intubation and tracheostomy, and risk of death [2,3].…”
Section: Introductionmentioning
confidence: 99%